Characterization and calibration of a novel detection system for real time monitoring of radioactive contamination in water processed at water treatment facilities. (August 2017) - Carconi, P.; De Felice, P.; Fazio, A.; Petrucci, A.; Lunardon, M.; Moretto, S.; Stevanato, L.; Cester, D.; Pastore, P.
Abstract: Characterization and calibration measurements were carried out at the National Institute of Ionizing Radiation Metrology of ENEA on the TAp WAter RAdioactivity (TAWARA) Real Time Monitor system recently developed for real time monitoring of radioactive contamination in water processed at water treatment facilities. Reference radiations and radionuclides were chosen in order to reflect energy ranges and radiation types of the major water radioactive contaminants possibly arising from environmental, industrial or terroristic origin. The following instrument parameters were tested: sensitivity, selectivity, background, short/long term stability, linearity with respect to activity. Highlights: TAWARA system developed for radiological monitoring in water treatment facilities. Characterization and calibration measurements carried out at ENEA in Italy. Sensitivity, selectivity, background, short/long term stability and linearity were tested.